Literature Review: The Role Of Human Resource Management In Healthcare Services - Dewa Ayu Vania Novista Anjani; Muh. Agung Gunadi; Anak Agung Ngurah Mayun Trinanditya; Iman Illal Haqqni; Nurhaeni Sikki (Sean Institute, 2024)
The quality of healthcare services is crucial for improving public health, with Human Resource Management (HRM) playing a vital role. HRM involves managing individuals and teams within an organization to ensure optimal performance and alignment with organizational goals, encompassing recruitment, training, development, evaluation, and compensation. This literature review aims to enhance understanding of HRM's role in improving healthcare service quality, identify influencing factors, and offer recommendations to overcome obstacles in HRM. A qualitative research approach was employed to analyze and synthesize existing literature on HRM in healthcare services. Thematic analysis identified recurring themes in articles, papers, and books. We conducted a thorough search of databases and books, using relevant keywords to ensure comprehensive coverage. Effective HRM in healthcare includes the recruitment, training, development, and retention of healthcare professionals. Supportive work environments and strong managerial backing significantly enhance motivation and performance, ultimately improving patient care quality. However, many developing countries face HRM challenges, including workforce shortages, uneven distribution of healthcare professionals, and insufficient training opportunities. Additional issues involve inadequate training programs, bureaucratic obstacles, and administrative inefficiencies. Addressing these challenges through comprehensive HRM strategies can significantly improve healthcare delivery and workforce management. This literature review underscores the pivotal role of HRM in enhancing healthcare service quality. Through strategic recruitment, training, development, and retention of healthcare professionals, HRM fosters supportive work environments and managerial support, essential for enhancing healthcare worker motivation and performance, ultimately benefiting patient care. To address persistent challenges, tailored HRM strategies must adapt to environmental changes and prioritize ongoing training programs, administrative streamlining, and equitable workforce distribution policies. Understanding HRM's roles and challenges is essential for developing effective strategies to ensure a competent and motivated healthcare workforce, thereby continuously enhancing healthcare service quality.